Developing Interactive Andragogical Online Content for Nursing Students (LEARNing Landscapes, 2013)
There is currently a shortage of registered nurses. This situation is further complicated by increased demands for nurses who are baccalaureate or masters’ prepared. Online education can facilitate degree completion for working adults. Nursing faculty, however, are not always adequately prepared to teach online. The purpose of this article is to describe the results of a qualitative research study and thematic analysis of methods utilized by nursing faculty currently involved in teaching online courses. Moreover, the article presents the experiences of nursing faculty who discovered creative methods to develop engaging online content based on relevant clinical experiences, and their transformation from teachers to facilitators of adult learning.
Keywords: online; technology; nursing; adult; qualitative; thematic analysis; teaching; online content; adult learning